2012
DOI: 10.1016/j.jcrs.2012.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral reading performance of 4 multifocal intraocular lens models and a monofocal intraocular lens under bright lighting conditions

Abstract: Drs. Grabner and Dexl were patent owners of the Salzburg Reading Desk technology (now owned by SRD-Vision, LLC). No other author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…Postoperatively, there were no statistically significant differences between the groups in reading speed, reading acuity, or critical print size measured at 70% and 100% contrast levels. Compared with the results described by Rasp et al, 35 our study found better reading acuity and speed but similar or slightly lower critical print size. A possible explanation is that our study population was younger than that described by Rasp et al Spectacle independence, a desired outcome of cataract surgery with multifocal IOLs, was high and in line with results in previous studies.…”
Section: Discussionsupporting
confidence: 65%
“…Postoperatively, there were no statistically significant differences between the groups in reading speed, reading acuity, or critical print size measured at 70% and 100% contrast levels. Compared with the results described by Rasp et al, 35 our study found better reading acuity and speed but similar or slightly lower critical print size. A possible explanation is that our study population was younger than that described by Rasp et al Spectacle independence, a desired outcome of cataract surgery with multifocal IOLs, was high and in line with results in previous studies.…”
Section: Discussionsupporting
confidence: 65%
“…For the purpose of statistical pooling, we only used the Alio study with larger sample size and the Allen study because it had the outcomes of interest. El-Maghraby 1992 37 Steinert 1992 16 Percival 1993 29Rosetti 1994 33 Allen 1996 18 Haaskjold 1998 17 Javitt 2000 19 Kamlesh 2001 30 Leyland 2002 31 Nijkamp 2004 20 Sen 2004 35 Marchini, 2007 15 Zeng, 2007 21 Cillino, 2008 26 Harman, 2008 21 Palmer, 2008 32 Zhao,2009 25 Alio, 2011 14 Alio, 2011 27 Jusufovic 2011 36 Ji, 2012 23 Peng, 2012 24 Rasp, 2012 34 Wilkins, 2013 13 Labiris, 2015 28 = low risk of bias = high risk of bias = unknown…”
Section: Description Of the Evidencementioning
confidence: 99%
“…Diffractive multifocal IOLs have been shown to provide better uncorrected near visual acuity, contrast sensitivity, reading performance and less photic phenomenon than that obtained with a refractive multifocal in some,7 8 but not all studies 9. In vitro optical testing also suggests that diffractive IOL designs should provide better optical quality and are more robust to tilt and decentration than concentric, refractive segmented IOLs 10.…”
Section: Introductionmentioning
confidence: 99%